Interest Rate Liberalization : Some Lessons From Africa - Turtelboom, Bart (IMF Working Papers; Working Paper ;, 1991)
This paper undertakes a survey of theoretical considerations and an analysis of the experience of five African countries with interest rate liberalization. Despite substantial progress in monetary policy reforms, liberalization has only partially affected the level and variability of interest rates. Several factors-macroeconomic instability, oligopolistic financial markets, the absence of developed capital markets, as well as the sequencing of the liberalization programs and the asymmetric availability of information-explain the increase in the spread between lending and deposit rates as well as the rather inflexible pattern of interest rates during the transition to a market-based financial system.